2004
DOI: 10.1007/s11904-004-0014-y
|View full text |Cite
|
Sign up to set email alerts
|

Management of antiretroviral therapy in neonates, children, and adolescents

Abstract: There have been tremendous advances in the prevention of maternal-to-child transmission of HIV and treatment of HIV-infected children and adolescents. Although multiple classes of anti-HIV drugs are available that can control viral replication and stabilize immune function when used in combination, patients and their providers must also manage complex and frequently toxic regimens. This article updates our original report that summarizes official National Institutes of Health guidelines for the prevention of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…1 , 41 This contrasts with the results of the International Maternal Pediatric Adolescent AIDS Clinical Trials Group (IMPAACT) 1060 trial (see Development of efavirenz resistance in children section) that found a significantly higher rate of virological failure, treatment discontinuation, or death at 24 weeks in children aged <3 years on nevirapine-regimens compared with lopinavir/ritonavir. 4 , 42 , 43 Switching from protease inhibitor-based regimens to NNRTI in order to simplify ART after virologic suppression can result in improvements in total cholesterol, low-density lipoprotein cholesterol, triglycerides, and the cholesterol/high-density lipoprotein cholesterol ratio, while maintaining virologic suppression and immunologic benefits. 5 , 44 …”
Section: Nnrti-based Versus Protease Inhibitor-based Arv Regimens In mentioning
confidence: 99%
See 1 more Smart Citation
“…1 , 41 This contrasts with the results of the International Maternal Pediatric Adolescent AIDS Clinical Trials Group (IMPAACT) 1060 trial (see Development of efavirenz resistance in children section) that found a significantly higher rate of virological failure, treatment discontinuation, or death at 24 weeks in children aged <3 years on nevirapine-regimens compared with lopinavir/ritonavir. 4 , 42 , 43 Switching from protease inhibitor-based regimens to NNRTI in order to simplify ART after virologic suppression can result in improvements in total cholesterol, low-density lipoprotein cholesterol, triglycerides, and the cholesterol/high-density lipoprotein cholesterol ratio, while maintaining virologic suppression and immunologic benefits. 5 , 44 …”
Section: Nnrti-based Versus Protease Inhibitor-based Arv Regimens In mentioning
confidence: 99%
“…The pathogenesis of HIV-1 and HIV-2 infection and the general virological and immunological principles underlying the use of ART are similar for all HIV-infected patients, but unique considerations exist for infected children. 4 Mother-to-child transmission represents the most common cause of pediatric HIV infection, the majority of cases occurring in the peripartum period. Postpartum infection of infants occurs primarily through breastfeeding, which globally accounts for roughly one third of all cases of perinatal HIV.…”
Section: Introductionmentioning
confidence: 99%